2020
DOI: 10.1007/s10646-020-02256-7
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin, diclofenac, ibuprofen and 17α-ethinylestradiol differentially affect the activity of acetogens and methanogens in anaerobic communities

Abstract: Pharmaceutical compounds end up in wastewater treatment plants but little is known on their effect towards the different microbial groups in anaerobic communities. In this work, the effect of the antibiotic Ciprofloxacin (CIP), the non-steroidal anti-inflammatory drugs Diclofenac (DCF) and Ibuprofen (IBP), and the hormone 17α-ethinylestradiol (EE2), on the activity of acetogens and methanogens in anaerobic communities, was investigated. Microbial communities were more affected by CIP, followed by EE2, DCF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…The effect of ciprofloxacin on the activity of acetogens and methanogens in anaerobic communities was investigated by Silva et al [ 35 ], who found acetogenic bacteria to be sensitive to ciprofloxacin concentrations above 1 mg/L, while hydrogenotrophic methanogens were not affected by any CIP concentration. Other authors [ 36 ] found that CIP caused a significant disturbance of anaerobic digestion at concentrations between 0.5 to 50 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ciprofloxacin on the activity of acetogens and methanogens in anaerobic communities was investigated by Silva et al [ 35 ], who found acetogenic bacteria to be sensitive to ciprofloxacin concentrations above 1 mg/L, while hydrogenotrophic methanogens were not affected by any CIP concentration. Other authors [ 36 ] found that CIP caused a significant disturbance of anaerobic digestion at concentrations between 0.5 to 50 mg/L.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies reported the effects of antibiotics on the Bacteria and Archaea domains [ 26 , 27 , 37 ], showing that macrolides inhibited more methanogens than Bacteria , in particular acetoclastic. Moreover, it must be considered that the Archaea component of the AD microbial community thrives by relying on Bacteria metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…SMX is a bacteriostatic antibiotic that primarily inhibits bacterial growth and reproduction by acting on folic acid synthesis [ 24 ]. Several studies evaluated the effects of CIP [ 25 , 26 , 27 ] and SMX on AD performance [ 28 , 29 ] and its microbial community. Although this research is of great interest, usually more than one antibiotic is detected in manure or digestate [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some previous works also evaluated the effect of several pharmaceuticals on AD, where attention is specially focused on biogas production, but not to organic matter removal. In this manner, it was proven in the literature that IBU inhibits acetoclastic methanogens but does not cause inhibition to other trophic groups involved in the anaerobic process [49].…”
Section: Effect Of Ppcps On Organic Matter Removal and Biogas Productionmentioning
confidence: 91%